GPCR RAMP interactome - Dahl, Leo (SciLifeLab Serve, 2026)
Visualizations of the results from an interaction screen of 215 G protein-coupled receptors (GPCRs) and the receptor activity–modifying proteins (RAMPs). Companion app to 'Multiplexed mapping of the interactome of GPCRs with receptor activity–modifying proteins', https://doi.org/10.1126/sciadv.ado9959